Interventional effects of modified constraint-induced movement therapy on upper limb function in patients who had a stroke: systematic review and meta-analysis - Cheng Wang; Jian Liu; Zizhuo Wang; Yunong Zhang (BMJ Open)
Objectives To systematically evaluate the intervention effect of modified constraint-induced movement therapy (m-CIMT) on upper limb function in patients who had a stroke.Design Systematic review and meta-analysis.Data sources A computer-based search was conducted in PubMed, Cochrane Library, Embase, Web of Science and China National Knowledge Infrastructure for randomised controlled trials (RCTs) on the intervention effect of m-CIMT on upper limb function in patients who had a stroke, with the search conducted up until 23 May 2024.Eligibility criteria We included only RCTs in which patients who had a stroke performed m-CIMT or m-CIMT in addition to the control group, and the outcome was upper limb function.Data extraction and synthesis Data extraction and synthesis used the reporting checklist for systematic review based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. The risk of bias and methodological quality of included studies were evaluated by two independent investigators under the guidance of Cochrane risk of bias. Effect sizes were pooled, funnel plots were created and subgroup analyses were conducted using Stata V.17.0. If I²>50%, a random-effects model was applied; otherwise, a fixed-effects model was used. Publication bias was assessed through funnel plots and Egger’s test. In the presence of publication bias, a trim-and-fill method was employed for further examination. The quality of evidence was evaluated using GRADEpro.Results A total of 16 studies including 612 patients were included. Rehabilitation outcomes were assessed using the Fugl–Meyer Assessment (I²=90.34%), Motor Activity Log—Quality of Movement (I²=36.02%), Motor Activity Log—Amount of Use (I²=65.76%), Action Research Arm Test (I²=62.66%) and the Wolf Motor Function Test (I²=36.78%). Low-level evidence suggests that m-CIMT improves upper limb function in patients who had a stroke (all p<0.05). Subgroup analyses indicate that m-CIMT is effective in patients with ‘chronic stroke’ (p=0.001) and in patients who had a stroke with a course duration of ‘>2 months’ (p=0.005). Intervention periods of ‘2–4 weeks’ (p=0.008) and ‘5–12 weeks’ (p<0.01), as well as intervention durations of ‘30–60 min’ (p=0.006) and ‘120–180 min’ (p=0.045), were all found to improve upper limb function in patients who had a stroke.Conclusion Low-level evidence suggests that m-CIMT can improve upper limb function in patients who had a stroke, although some indicators exhibit high heterogeneity. Therefore, this conclusion should be interpreted with caution. m-CIMT appears to improve upper limb function in patients who had a stroke with a course duration of more than 2 months, as well as in patients with chronic stroke. The intervention period should be at least 2 weeks, and each training session should last at least 30 min. Future studies should adopt more rigorous methodologies and larger sample sizes to further validate the efficacy of m-CIM.PROSPERO registration number CRD42024550028.